Perbandingan Sistem Pengawasan Lembaga Antikorupsi Di Asia Pasifik - Nafiatul Munawaroh (Lex Renaissance, 2021)
This study discusses the comparison of the monitoring system of anti-corruption institutions in Asia-Pacific countries, including Indonesia, Hong Kong, Malaysia, Myanmar, and Singapore. Through this comparative study, it is hoped that there will be a more proportional formulation of a supervisory system for anti-corruption institutions, especially in Indonesia. This study uses a normative juridical legal research method with a comparative approach. The legal materials used are primary and secondary legal materials obtained through literature studies and analyzed in a normative juridical manner. This study concludes that the comparative analysis of the anti-corruption agency supervisory system in Asia-Pacific, there are three trends. Low supervision system (laden with intervention) with low political will like Myanmar, proportional supervision but relatively low political will – both like Indonesia and Malaysia, and classic monitoring system (by executive, legislative and internal) but high political will like Hong Kong and Singapore.Key Words: Anti-corruption institution; supervision; supervisory boardAbstrakPenelitian ini membahas mengenai perbandingan sistem pengawasan lembaga anti korupsi di negara-negara Asia Pasifik, di antaranya Indonesia, Hong Kong, Malaysia, Myanmar, dan Singapura. Melalui studi perbandingan ini diharapkan akan ada formulasi sistem pengawasan terhadap lembaga anti korupsi yang lebih proporsional terutama di Indonesia. Penelitian ini menggunakan metode penelitian hukum yuridis normatif dengan pendekatan perbandingan (comparative approach). Bahan hukum yang digunakan adalah bahan hukum primer dan sekunder yang diperoleh melalui studi pustaka dan dianalisis secara yuridis normatif. Penelitian ini menyimpulkan, bahwa analisis perbandingan sistem pengawasan lembaga anti-korupsi di Asia-Pasifik, terdapat tiga kecenderungan. Sistem pengawasan rendah (sarat intervensi) dengan political will rendah seperti Myanmar, pengawasan yang proporsional namun political will relatif rendah – baik seperti Indonesia, dan Malaysia, dan sistem pengawasan klasik (oleh eksekutif, legislatif dan internal) namun political will tinggi seperti Hong Kong dan Singapura.Kata Kunci: Lembaga anti-korupsi; pengawasan; dewan pengawas